MEMBANGUN MENTAL SANTRI MELALUI PUASA SUNNAH 40 HARI(Studi di Pondok Pesantren Darul Amanah Sukorejo Kendal) - Muhammad Fatwa; Millatus Sa'diyah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
Intellectual education needs to be balanced with mental development to prevent students (santri) from experiencing inner conflicts and psychosomatic disorders. Fasting is one method of purifying the soul and a source of inner peace through drawing closer to Allah SWT. The 40-day sunnah fasting practiced at Pondok Pesantren Darul Amanah Sukorejo Kendal significantly contributes to shaping students' social sensitivity, self-confidence, self-control, patience, honesty, and emotional stability. This practice serves as a preventive strategy against psychological pressure rooted in the dominance of desires, which is the main cause of mental disorders. Therefore, the 40-day fasting plays a vital role in stabilizing mental health and optimizing the development of students’ personality in a productive and dynamic manner